Solve an equations using substitution practice solve the system of equations x = 6 y - 3 2x + 7y = 13

1 answer

First, we can substitute the value of x from the first equation into the second equation:

x = 6y - 3

2(6y - 3) + 7y = 13

12y - 6 + 7y = 13

19y - 6 = 13

19y = 19

y = 1

Now that we have found the value of y, we can substitute it back into the first equation to find the value of x:

x = 6(1) - 3

x = 6 - 3

x = 3

Therefore, the solution to the system of equations is x = 3 and y = 1.
Similar Questions
  1. 1. For the following system of equations, what is the x-value of the solution?-x+2y=6 6y=x+18 a. -18 b. 0*** c. -6 d. 3 2. Solve
    1. answers icon 48 answers
  2. 1. Solve the system of two linear equations.-3x - 4y = -23 3x - 5y = 5 2. How many solutions does the system of equations have?
    1. answers icon 7 answers
  3. Solve the system of two equations using substitution.y=2+3x 4x−3y=−16 (1 point) ___________________________________ 2.)
    1. answers icon 1 answer
    1. answers icon 2 answers
more similar questions